Exposure modifiers of the relationships of transportation noise with high blood pressure and noise annoyance - Babisch, Wolfgang; Swart, Wim; Houthuijs, Danny; Selander, Jenny; Bluhm, Gösta; Pershagen, Göran; Dimakopoulou, Konstantina; Haralabidis, Alexandros S.; Katsouyanni, Klea; Davou, Elli; Sourtzi, Panayota; Cadum, Ennio; et al. (The Journal of the Acoustical Society of America, 2012)
In the cross-sectional hypertension and exposure to noise near airports study the relationship between road traffic noise, aircraft noise and hypertension and annoyance was investigated. The data collection comprised a variety of potentially exposure modifying factors, including type of housing, location of rooms, window opening habits, use of noise-reducing remedies, shielding due to obstacles, lengths of exposure. In the present paper the quantitative role of these factors on the relationship between road and aircraft noise exposure and outcomes was analyzed. Multiple logistic and linear regression models were calculated including these co-factors and related interaction terms with noise indicators, as well as stratified analyses. Type of housing, length of residence, location of rooms and the use of noise reducing remedies modified the relationship between noise and hypertension. However, the effects were not always in the direction of a stronger association in higher exposed subjects. Regarding annoyance, type of housing, location of rooms, noise barriers, window opening habits, noise insulation, the use of noise reducing remedies, hours spent at home during daytime were significant effect modifiers. The use of noise-reducing remedies turned out to be indicators of perceived noise disturbance rather than modifiers reducing the annoyance.